Characterization of Edible Film Made from Glucomannan Konjac Flour Modified Polyvinyl Alcohol (PVA) and Sorbitol as Plasticizer - Hantoro Satriadi; W Widayat; Bernike Vemmialia Jonfita; Nabilla Salma Listyawijayanti (Journal of Bioresources and Environmental Sciences, 2025)
Edible film is a thin layer for primary packaging of food consisting of consumable components. In general, the purpose of this research is to examine the mechanical and physical properties of edible film in the influence of the addition of PVA and sorbitol as plasticizers and get the best edible film characteristics to be used as food packaging materials. The weight variations of porang flour used were 5 grams, 6 grams, 7 grams, 8 grams, and 9 grams. With sorbitol volume of 1 ml, 2 ml, and 3 ml, 4 ml, and 5 ml, and PVA mass of 3%, 4%, 5%, 6%, and 7% (b/v). The drying operation temperature was 40oC, 50oC, 60oC, 70oC, 80oC and the drying time was 12 hours and 24 hours. Then the thickness test, mechanical test, water resistance and solubility test, water vapor transmission test, and SEM (Scanning Electron Microscope) analysis were analysed. The best results are with variations of porang flour 6 grams, sorbitol 5 ml, PVA 5%, drying temperature 40℃, and drying time for 12 hours. The more sorbitol is added, the thickness, water resistance, water solubility, and elongation of the edible film will increase. The addition of konjac flour increases the thickness, water resistance, water solubility, tensile strength, and elongation of the edible film. However, it is inversely proportional to the water vapor transmission of edible film which has decreased.